Organizational systems in british sport and their impact on athlete development and mental health - Poucher, Z. A.; Tamminen, K. A.; Wagstaff, C. R. D. (The Sport Psychologist, 2021)
Sport organizations have been noted as pivotal to the success or failure of athletes, and sport environments can impact the well-being and development of athletes. In this study, the authors explored stakeholders` perceptions of how high-performance sport organizations support athlete development. Semistructured interviews were conducted with 18 stakeholders from the United Kingdom`s high-performance sport system and transcripts were analyzed using a semantic thematic analysis. Participants emphasized the importance of performance lifestyle advisors, sport psychologists, and financial assistance for promoting athlete development. Several stakeholders observed that despite the extensive support available to athletes, many do not engage with available support, and the prevalence of a performance narrative has led to an environment that discourages holistic development. It follows that sport organizations could develop alternative strategies for promoting athletes` access to and engagement with available supports, while funding agencies might broaden existing funding criteria to include well-being or athlete development targets.